Caracterização de escória de conversor a oxigênio obtida no processo BSSF antes e após tratamento hidrometalúrgico - Souza, Ticiane Vieira de Paula (2016)
Metallurgical slags have been studied and should be considered as subproducts of the steel industry with economic value. LD BOS slags contain high content of iron oxide because they are produced in oxidant conditions, and due to this fact these particular slags are not suitable for Portland ciment production. In the present work a BSSF slag (a converter slag) which was treated by the BSSF process was characterized and then a new hydrometallurgical process for separating iron oxides from white oxides is proposed was created. With this new process it was possible to obtain two solid parts: (i) a material with high iron oxide content, which can be used as chilling agente in the BOF, and (ii) a material with high content of white oxides, which can be useful for the cement industry. In The sample was got from a Corean steelworks, and from it was possible to determine for the BSSF slag behavior: (i) its paramagnetic behaviour, (ii) the presence of Fe2+ , (iii) the elements and phases. Also it was possible to verify that the material doesn’t have metal iron in its composition and was possible quantify the elements and phases presents in the sample. The following techniques where used: Mössbauer espectroscopy, magnetic analysis (VSM), scanning eléctron microscopy, x-ray fluorescence, x-ray diffraction. The calculated Fe recovery from the BSSF slag is 95,8 wt% (in the Fe-rich part after the hydrometallurgical treatment). It is concluded from this study that the separating iron oxides methodology proposed is promising for treatment of LD slags the present study can be used as a reference for separating iron oxides from white oxides of BOS slag which was treated by the BSSF process.